Induction of c-jun protooncogene expression and transcription factor AP-1 activity by the polyoma virus middle-sized tumor antigen. - Schönthal, A (1992)
Polyoma virus middle-sized tumor (PymT) antigen is required for neoplastic cell transformation by polyoma virus. We studied changes in gene expression accompanying expression of PymT in murine fibroblasts. These experiments showed that PymT differentially affects several growth-related genes. c-jun protooncogene expression was highly increased, whereas the expression of two growth arrest-specific genes (gas) was reduced, in cells transformed by PymT. Cotransfection experiments showed that the increase in c-jun expression resulted from elevated activity of the transcription factor AP-1 and was mediated through the phorbol 12-tetradecanoate 13-acetate response element in the c-jun promoter. The degree of c-Jun/AP-1 activation by different PymT mutants correlated with their transforming capability, suggesting that regulation of c-Jun/AP-1 activity may play a role in cell transformation by polyoma virus.